2017
DOI: 10.1177/0194599817707514
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Otologic and Audiometric Outcomes in Patients with Cleft Palate

Abstract: Objective Describe longitudinal audiometric and otologic outcomes in patients with cleft palates. Study Design Case series with chart review. Setting Single academic medical center. Methods Charts of 564 patients with a diagnosis of cleft palate (59% syndromic etiology, 41% nonsyndromic) from 1998 to 2014 were reviewed. Patients without at least 1 audiometric follow-up were excluded from analysis. Patient demographics, surgeries, audiometric tests, and otologic data were recorded for 352 patients. Results Fort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 38 publications
3
34
0
Order By: Relevance
“…Chronic Eustachian tube dysfunction today is a well‐recognized phenomenon in children with cleft palate for which the natural history is further characterized by the results of this study. Previous work has described effective use of proactive treatment of otitis media with effusion by routine placement of tympanostomy tubes in this patient population, but the length of time for which we should be proactive is not precisely known . It has been shown that middle ear disease, while widely prevalent in children with cleft palate ages 4 through 6 years, generally presents with a lower burden of disease by age 12 years .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic Eustachian tube dysfunction today is a well‐recognized phenomenon in children with cleft palate for which the natural history is further characterized by the results of this study. Previous work has described effective use of proactive treatment of otitis media with effusion by routine placement of tympanostomy tubes in this patient population, but the length of time for which we should be proactive is not precisely known . It has been shown that middle ear disease, while widely prevalent in children with cleft palate ages 4 through 6 years, generally presents with a lower burden of disease by age 12 years .…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has described effective use of proactive treatment of otitis media with effusion by routine placement of tympanostomy tubes in this patient population, but the length of time for which we should be proactive is not precisely known. [17][18][19][20] It has been shown that middle ear disease, while widely prevalent in children with cleft palate ages 4 through 6 years, generally presents with a lower burden of disease by age 12 years. 7 In a prior crosssectional analysis of children with cleft palate, Handzic-Cuk et al also demonstrated that the median age for type A tympanograms at their institution was 11 years.…”
Section: Discussionmentioning
confidence: 99%
“…Imbery et al revealed the importance of routine follow-up care by an otolaryngologist to minimize the complications of ear disease. The rate of cholesteatoma formation was reduced from 9% to 3% when a coordinated team approach was instituted to care for the orofacial cleft patients [ 17 ]. Once again stressing on the significance of routine ear check-ups, Goudy S et al claimed that 50% of orofacial cleft children continue to suffer from ear diseases as adults, making it a difficult situation to manage [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with ventilation tubes (VT) are very common in children with CP±L, often at the time of the palatal repair. The optimal time for VT insertion and the risk for complications as otorrhea, myringosclerosis, retraction, perforation and granulation of the tympanic membrane, permanent hearing impairment, and post-VT insertion cholesteatoma has been discussed in many studies (Imbery et al, 2017;Karanth and Whittemore, 2018;Klockars and Rautio, 2012;Phua et al, 2009;Ponduri et al, 2009;Shaffer et al, 2018). In a systematic review by Kuo and colleagues, post-VT complications and sequelae are described in seven articles.…”
Section: Treatment With Ventilation Tubes and Risk For Following Compmentioning
confidence: 99%